Executing parallel logical operations with DNA - Ogihara, M.; Ray, A. (Proceedings of the 1999 Congress on Evolutionary Computation, CEC99 : July 6-9, 1999, Mayflower Hotel, Washington, D.C., USA, 1999)
DNA computation investigates the potential of DNA as a massively parallel computing device. Research is focused on designing parallel computation models executable by DNA based chemical processes and on developing algorithms in the models. L. Adleman (1994) initiated this area of research by presenting a DNA based method for solving the Hamilton Path Problem. That contribution raised the hope that parallel computation by DNA could be used to tackle NP-complete problems which are thought of as intractable. The current realization however, is that NP-complete problems may not be best suited for DNA based (more generally, molecule based) computing. A better subject for DNA computing could be large scale evaluation of parallel computation models. Several proposals have been made in this direction. We overview those methods, discuss technical and theoretical issues involved, and present some possible applications of those methods.